Impact of Intensive Versus Standard Blood Pressure Management by Tertiles of Blood Pressure in SPRINT (Systolic Blood Pressure Intervention Trial). Issue 6 (June 2018) - Shapiro, Brian P.; Ambrosius, Walter T.; Blackshear, Joseph L.; Cushman, William C.; Whelton, Paul K.; Oparil, Suzanne; Beddhu, Srinivasan; Dwyer, Jamie P.; Gren, Lisa H.; Kostis, William J.; Lioudis, Michael; Pisoni, Roberto; et al.
Abstract : Intensive systolic blood pressure (SBP) control improved outcomes in SPRINT (Systolic Blood Pressure Intervention Trial). Our objective was to expand on reported findings by analysis of baseline characteristics, primary outcomes, adverse events, follow-up blood pressure, and medication use differences by baseline SBP (tertile 1 [T1], <132; tertile 2 [T2], 132–145; and tertile 3 [T3], >145 mm Hg). Participants with higher baseline SBP tertile were more often women and older, had higher cardiovascular risk, and lower utilization of antihypertensive medications, statins, and aspirin. Achieved SBP in both treatment arms was slightly higher in T2 and T3 compared with T1 and fewer in the T3 groups achieved SBP targets compared with T1 and T2 groups. The primary composite outcome with intensive versus standard SBP treatment was reduced by 30% in T1, 23% in T2, and 17% in T3 with no evidence of an interaction ( P =0.77). Event rates were lower in the intensive arm, and there was no evidence that this benefit differed by SBP tertile. There was no difference in the hazard for serious adverse events in any of the 3 tertiles. Medication utilization differed across the SBP tertiles at baseline with a lesser percentage of diuretics and angiotensin-converting enzyme inhibitors/angiotensin receptor blocker drugs in the higher tertiles—a finding that reversed during the trial. The beneficial effects of intensive SBP lowering were not modified by the level of baseline SBP. Within the parameters of this population, these findings add support for clinicians to treat blood pressure to goal irrespective of baseline SBP. Abstract : Supplemental Digital Content is available in the text.